2000
DOI: 10.1046/j.1440-1789.2000.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Widespread calcium deposits, as detected using the alizarin red S technique, in the nervous system of rats treated with dimethyl mercury

Abstract: It has been reported that the alizarin red S technique may be used to visualize both intracellular and extracellular calcium deposits. Using this method histologic observations of the nervous system were made in rats that were given dimethyl mercury at 5 mg/kg per day for 12 consecutive days, and killed on days 1, 4, 7, 10, 12, 24, 32, 49, 100 and 140 (day 0 was the day that the final dose was administered). Neuronal degeneration with calcium deposition was found in the nervous system from day 4 onward. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
1
19
1
Order By: Relevance
“…Thus, mineralized cells shared ultrastructural features in both control and OGD-lesioned slices; microcalcification was specifically associated with mitochondria but not other organelles. This novel type of mineralization and cell death are in contrast with a previous in vivo finding that intracellular calcification initially occurs in the mitochondria of degenerating neurons, proceeds to fill the dead cell, and even extends beyond cells Mori et al, 2000;Nitsch and Scotti, 1992;Simon et al, 1984;Sztriha et al, 1985). This may be attributable to the nature of slice cultures because early recognition of cell debris by infiltrating macrophages is absent, thus resulting in the slow progression of degenerative processes during culture.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Thus, mineralized cells shared ultrastructural features in both control and OGD-lesioned slices; microcalcification was specifically associated with mitochondria but not other organelles. This novel type of mineralization and cell death are in contrast with a previous in vivo finding that intracellular calcification initially occurs in the mitochondria of degenerating neurons, proceeds to fill the dead cell, and even extends beyond cells Mori et al, 2000;Nitsch and Scotti, 1992;Simon et al, 1984;Sztriha et al, 1985). This may be attributable to the nature of slice cultures because early recognition of cell debris by infiltrating macrophages is absent, thus resulting in the slow progression of degenerative processes during culture.…”
Section: Discussioncontrasting
confidence: 74%
“…We examined the extent and topography of calcification using alizarin red S staining, which is a sensitive and specific method for detecting calcium deposition (Mori et al, 2000;Nitsch and Scotti, 1992), and the osmium/potassium-bichormate method to precipitate and ultrastructurally visualize endogenous calcium (Probst, 1986). Finally, we employed field emission-transmission electron microscopy (FE-TEM) equipped with EDAX (Energy Dispersive X-ray Analysis)…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular accumulation of Ca 2? was also observed in rats treated with dimethylmercury by injection at 5 mg/kg/day for 12 days (Mori et al 2000). Ca 2?…”
Section: Introductionmentioning
confidence: 75%
“…This spatiotemporal progression of calcification after ischaemic insult appears to be very closely comparable to the OPN expression pattern observed in our study. In addition, several lines of inquiry have revealed that intracellular calcification initially occurs in the mitochondria of degenerating neurons and subsequently propagates throughout the whole cell after brain insults54555657. What leads to intramitochondrial OPN expression is not certain, but it can be inferred that OPN is initially localised in degenerating mitochondria where initial intracellular calcification occurs, and then accumulates in the periphery of the degenerating neurites from where calcification subsequently spreads to the entire dendroplasm.…”
Section: Discussionmentioning
confidence: 99%